Produksi Tanaman Kedelai (Glycine max L. Merrill) Terhadap Pemberian Bradyrhizobium sp dan Kapur di Tanah Mineral Masam - Irda Nila Selvia (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2024)
Most Indonesians rely on soybean as their primary source of vegetable protein. Soybean is an agricultural commodity that serves as a basic ingredient in foods such as tofu, tempeh, soy sauce, tauco, oncom, etc. Soybean, as a vegetable protein, is cheaper and more accessible to Indonesians than animal protein. Currently, soybean yield is unable to meet market demand. Therefore, efforts are needed to increase soybean yield by applying Bradyrhizobium sp. and lime to acidic mineral soils to optimize soybean yield on the land. The research used a factorial randomized block design (RBD) with two factors on a 2 × 2 m plot in Cengkeh Turi Village, Binjai. The first factor was the inoculation of Bradyrhizobium sp. inoculants, which included BGR 3, LP 3, and no inoculant. The second factor was liming, which included not supplying and supplying lime at a level of 1.06 kg/plot (pH 4.5 to 5.5). The results showed that the BGR 3 inoculant was able to increase the number of filled pods of soybean plants. The application of lime was able to increase the number of productive branches, the number of filled pods, the dry weight of seeds per plant and the dry weight of 100 soybean seeds. The application of lime was able to increase the dry weight of seeds per plant by 22.17% and increase the dry weight of 100 seeds by 6.72%.